2007
DOI: 10.1038/nature06055
|View full text |Cite
|
Sign up to set email alerts
|

Tip60 is a haplo-insufficient tumour suppressor required for an oncogene-induced DNA damage response

Abstract: The acetyl-transferase Tip60 might influence tumorigenesis in multiple ways. First, Tip60 is a co-regulator of transcription factors that either promote or suppress tumorigenesis, such as Myc and p53. Second, Tip60 modulates DNA-damage response (DDR) signalling, and a DDR triggered by oncogenes can counteract tumour progression. Using E(mu)-myc transgenic mice that are heterozygous for a Tip60 gene (Htatip) knockout allele (hereafter denoted as Tip60+/- mice), we show that Tip60 counteracts Myc-induced lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
290
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 307 publications
(316 citation statements)
references
References 41 publications
25
290
1
Order By: Relevance
“…By real-time PCR analysis, we found that Tip60 mRNA is underexpressed in 72 out of 74 cancers (T) compared to adjacent normal (N) tissue (Figure 1a; see Supplementary data 2 for all T/N ratios). This decrease is highly significant (Po0.000001, one-sided binomial exact test) and was expected because similar results were already reported (Lleonart et al, 2006;Gorrini et al, 2007). Importantly, sequencing of the entire Tip60 cDNA in four tumoral samples shows that Tip60, although underexpressed, is not mutated in tumors.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…By real-time PCR analysis, we found that Tip60 mRNA is underexpressed in 72 out of 74 cancers (T) compared to adjacent normal (N) tissue (Figure 1a; see Supplementary data 2 for all T/N ratios). This decrease is highly significant (Po0.000001, one-sided binomial exact test) and was expected because similar results were already reported (Lleonart et al, 2006;Gorrini et al, 2007). Importantly, sequencing of the entire Tip60 cDNA in four tumoral samples shows that Tip60, although underexpressed, is not mutated in tumors.…”
Section: Resultssupporting
confidence: 85%
“…Taken together, these data suggest that a decrease of Tip60 function is likely to be causal for colon cancer progression by preventing apoptosis. In agreement with this possibility, a twofold decrease of Tip60, which is within the range of what we observe in colorectal cancer, favors tumorigenesis in a mouse model of lymphoma (Gorrini et al, 2007). This haploinsufficient tumor suppressor effect has been attributed to a function of Tip60 in the DDR pathway induced by oncogenic stress, which is a known anticancer pathway in mammals.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations